Modelling risks for electric power markets. (2012)
This paper presents a study of the Forward Risk Premia (FRP) in Wholesale Electric Power Market in Colombia (WPMC) showing how the FRP varies throughout the day and how its properties are explained by risk factors. It also shows that expected forward risk premia depends on factors such as variations in expected spot prices, due to the climatic conditions generated by the Oceanic Niño Index (ONI) and its impact on the available quantity of water to generate electric power. This document provides a quantitative assessment of the Colombian electricity forward price premium as defined as the discrepancy between spot and forward prices in the Colombian market. The study applies appropriate methodologies including linear regression and GARCH modeling of time series to investigate the issue under concern. It delivers empirical results which, to the best of our knowledge, are new in the market context of Colombia. In particular, the relation between a weather-linked phenomenon such as El Niño effect and electric forward price premia is quantified.